Back Cover: Integrated energy conversion units in nanoscale frameworks induce sustained generation and amplified lethality of singlet oxygen in oxidative therapy of tumor (View 6/2022). Issue 6 (19th December 2022) - Zhu, Jing; Ding, Tao; Jin, Kaifei; Xing, Yuxin; Huang, Jixi; Xia, Daqing; Cai, Kaiyong; Zhang, Jixi
Abstract : Rationally modulated MOF nanoparticles, which confine the chemodynamic catalysis site, the chemoluminescence transducer and the photodynamic ligand (three gears), constituted a cascade conversion system. The coupled processes in the nano‐confined space potentiated the sustained generation and amplified lethality of ROS, and in turn, induced endoplasmic reticulum stress‐mediated apoptosis and autophagy in tumor therapy.